2022
DOI: 10.3390/vaccines10081300
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Novel Peptide-Based Multi-Epitope Vaccine to Evoke a Robust Immune Response against Pathogenic Multidrug-Resistant Providencia heimbachae

Abstract: Providencia heimbachae, a Gram -ve, rod-shaped, and opportunistic bacteria isolated from the urine, feces, and skin of humans engage in a wide range of infectious diseases such as urinary tract infection (UTI), gastroenteritis, and bacteremia. This bacterium belongs to the Enterobacteriaceae family and can resist antibiotics known as multidrug-resistant (MDR), and as such can be life-threatening to humans. After retrieving the whole proteomic sequence of P. heimbachae ATCC 35613, a total of 6 non-homologous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The simulations’ results showed that the response could generate memory cells and chemokines that stimulate B-cell and humoral reactions. The effective use of molecular dynamics simulations and the accuracy of computational tools has been confirmed previously [ 44 , 45 , 46 ]. Indicators such as macrophages and dendritic cells also showed signs of memory cell formation.…”
Section: Discussionmentioning
confidence: 62%
“…The simulations’ results showed that the response could generate memory cells and chemokines that stimulate B-cell and humoral reactions. The effective use of molecular dynamics simulations and the accuracy of computational tools has been confirmed previously [ 44 , 45 , 46 ]. Indicators such as macrophages and dendritic cells also showed signs of memory cell formation.…”
Section: Discussionmentioning
confidence: 62%
“…This study, exploiting the NP’s nature has targeted the protein for the evaluation of potential T-cell and B-cell restricted epitopes. Similar methods have been utilized to form multi-epitope [ 13 ] and mRNA-based vaccines [ 42 , 43 ] for several other health issues recently.…”
Section: Discussionmentioning
confidence: 99%
“…The finalized epitopes were aligned with the help of linkers (to maintain the individual epitope domains), an adjuvant (to improve the entry and immunogenicity of the vaccine candidate), and an additional peptide for cell penetration of the construct. Previous studies by Sanchez et al (2021) [23] and [24] were followed to design the construct.…”
Section: Final Vaccine Constructmentioning
confidence: 99%